2010
DOI: 10.1210/endo.152.2.zee741a
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Is More Potent Than Vitamin D2 in Humans

Abstract: This article appears in The Journal of Clinical Endocrinology & Metabolism, published December 22, 2010, 10.1210/jc.2010-2230

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
10
0
5
Order By: Relevance
“…There is no general consensus as to whether the mushroom source D 2 is equally as effective as the animal source D 3 . Indeed, some studies have demonstrated that vitamin D 3 is more efficient than vitamin D 2 [21], while other studies have shown that vitamin D 2 and vitamin D 3 treatment yield equivalent outcomes in the treatment of hypovitaminosis D among young children [22]. What can be stated is that plant sources of vitamin D 2 are more sustainable than D 3 sources of animal origin [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is no general consensus as to whether the mushroom source D 2 is equally as effective as the animal source D 3 . Indeed, some studies have demonstrated that vitamin D 3 is more efficient than vitamin D 2 [21], while other studies have shown that vitamin D 2 and vitamin D 3 treatment yield equivalent outcomes in the treatment of hypovitaminosis D among young children [22]. What can be stated is that plant sources of vitamin D 2 are more sustainable than D 3 sources of animal origin [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is increasing evidence to support the combination use of calcium (500 mg daily) with vitamin D. 41 Vitamin D3 is preferable to vitamin D2 as a supplement because of its longer half life and stronger potency, leading to 2e3 times greater storage after administration. 57 Serum calcium, phosphorus, ALP, 25(OH)D, PTH levels, and urine calcium to creatinine ratios with radiography should be monitored after treatment. 7 Adult vitamin D repletion depends on baseline serum 25(OH)D concentration and effective absorptive capacity.…”
Section: Vitamin D Supplementationmentioning
confidence: 99%
“…En el caso de los efectos de la vitamina D 2 , que representa la forma más comúnmente ingerida, pocos han sido los estudios que evalúen sus efectos en modelos experimentales, basados en ensayos clínicos (16,17) que han sugerido que su potencia y duración de acción serían menores que las obtenidas con el uso de vitamina D 3. A pesar de ello, el presente estudio demuestra que los efectos en los niveles de glicemia son similares, no habiendo diferencias significativas entre ninguna dosis de los grupos de estudio que usaron vitamina D 2 y vitamina D 3 .…”
Section: Discussionunclassified